Hepatic ketogenesis is not required for starvation adaptation in mice - Kyle Feola; Andrea H. Venable; Tatyana Broomfield; Morgan Villegas; Xiaorong Fu; Shawn Burgess; Sarah C. Huen (Elsevier, 2024)
Objective: In response to bacterial inflammation, anorexia of acute illness is protective and is associated with the induction of fasting metabolic programs such as ketogenesis. Forced feeding during the anorectic period induced by bacterial inflammation is associated with suppressed ketogenesis and increased mortality. As ketogenesis is considered essential in fasting adaptation, we sought to determine the role of ketogenesis in illness-induced anorexia. Methods: A mouse model of inducible hepatic specific deletion of the rate limiting enzyme for ketogenesis (HMG-CoA synthase 2, Hmgcs2) was used to investigate the role of ketogenesis in endotoxemia, a model of bacterial inflammation, and in prolonged starvation. Results: Mice deficient of hepatic Hmgcs2 failed to develop ketosis during endotoxemia and during prolonged fasting. Surprisingly, hepatic HMGCS2 deficiency and the lack of ketosis did not affect survival, glycemia, or body temperature in response to endotoxemia. Mice with hepatic ketogenic deficiency also did not exhibit any defects in starvation adaptation and were able to maintain blood glucose, body temperature, and lean mass compared to littermate wild-type controls. Mice with hepatic HMGCS2 deficiency exhibited higher levels of plasma acetate levels in response to fasting. Conclusions: Circulating hepatic-derived ketones do not provide protection against endotoxemia, suggesting that alternative mechanisms drive the increased mortality from forced feeding during illness-induced anorexia. Hepatic ketones are also dispensable for surviving prolonged starvation in the absence of inflammation. Our study challenges the notion that hepatic ketogenesis is required to maintain blood glucose and preserve lean mass during starvation, raising the possibility of extrahepatic ketogenesis and use of alternative fuels as potential means of metabolic compensation.